2011
DOI: 10.1158/0008-5472.can-11-0364
|View full text |Cite
|
Sign up to set email alerts
|

miR-152 Is a Tumor Suppressor microRNA That Is Silenced by DNA Hypermethylation in Endometrial Cancer

Abstract: The etiology and development of human cancers that remain little understood might be enlightened by defining tumor suppressor microRNAs (TS-miRNA). In this study, we identified TS-miRNAs silenced by aberrant DNA hypermethylation in endometrial cancer. Functional screening of 327 synthetic miRNAs in an endometrial cancer cell proliferation assay identified 103 miRNAs that inhibited cell growth. We then determined the sequence, DNA methylation status, and expression levels of these miRNAs in endometrial cancer c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
163
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(172 citation statements)
references
References 32 publications
6
163
0
1
Order By: Relevance
“…The authors of one report have suggested that miR-152 acts as a tumor suppressor in prostate cancer by targeting the 3'UTR of TGF-α (Zhu et al, 2013). Other researchers reported epigenetic silencing by DNA hypermethylation of miR-152 in endometrial cancer, and restoration of miR-152 expression in endometrial cancer cell lines resulted in inhibition of tumor cell growth, both in vitro and in vivo (Tsuruta et al, 2011). However, in our study, we found that miR-152 could be induced by hypoxia and inhibited hypoxia-induced apoptosis in vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of one report have suggested that miR-152 acts as a tumor suppressor in prostate cancer by targeting the 3'UTR of TGF-α (Zhu et al, 2013). Other researchers reported epigenetic silencing by DNA hypermethylation of miR-152 in endometrial cancer, and restoration of miR-152 expression in endometrial cancer cell lines resulted in inhibition of tumor cell growth, both in vitro and in vivo (Tsuruta et al, 2011). However, in our study, we found that miR-152 could be induced by hypoxia and inhibited hypoxia-induced apoptosis in vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The ILK-Rictor complex acts as a potential molecular target for preventing/reversing fibrosis caused by EMT, cancer progression and metastasis (13). Tsuruta et al observed that Rictor, as a target gene of miR-152, participated in regulating the proliferation of cancer cells in endometrial carcinoma (10). Therefore, it was hypothesized that Rictor protein may be involved in the proliferation, migration and invasion of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, only a limited number of reports indicate that Rictor has certain biological functions in malignant tumors. For example, it has been reported that microRNA (miR)-152 acts as a tumor suppressor by targeting Rictor in gynecological cancers (10). Although Rictor may be involved in cancer progression, its expression in CRC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…miR-152 is located within an intron of COPZ2 and therefore it can be thought that this miRNA can be simultaneously expressed with the COPZ2 transcript. Indeed, it was found that the expression of these two transcripts are similar in human endometrial cancer cell lines (Tsuruta et al, 2011). Therefore it can be suggested that miR-152 is regulated via the intronic pathway.…”
Section: Ajimentioning
confidence: 99%